Verticillium dahliae transcription factor VdFTF1 regulates the expression of multiple secreted virulence factors and is required for full virulence in cotton. (31st July 2017) - Zhang, Wen‐Qi; Gui, Yue‐Jing; Short, Dylan P. G.; Li, Ting‐Gang; Zhang, Dan‐Dan; Zhou, Lei; Liu, Chun; Bao, Yu‐Ming; Subbarao, Krishna V.; Chen, Jie‐Yin; Dai, Xiao‐Feng
Summary: Fungal transcription factors (TFs) implicated in the regulation of virulence gene expression have been identified in a number of plant pathogens. In Verticillium dahliae, despite its agricultural importance, few regulators of transcription have been characterized. In this study, a T‐DNA insertion mutant with significantly reduced virulence towards cotton was identified. The T‐DNA was traced to VdFTF1, a gene encoding a TF containing a Fungal_trans domain. Transient expression in onion epidermal cells indicated that VdFTF1 is localized to the nucleus. The VdFTF1‐ deletion strains displayed normal vegetative growth, mycelial pigmentation and conidial morphology, but exhibited significantly reduced virulence on cotton, suggesting that VdFTF1 is required exclusively for pathogenesis. Comparisons of global transcription patterns of wild‐type and VdFTF1‐ deletion strains indicated that VdFTF1 affected the expression of 802 genes, 233 of which were associated with catalytic processes. These genes encoded 69 potentially secreted proteins, 43 of which contained a carbohydrate enzyme domain known to participate in pathogenesis during infection of cotton. Targeted gene deletion of one VdFTF1‐regulated gene resulted in significantly impaired vascular colonization, as measured by quantitative polymerase chain reaction, as well as aggressiveness and symptom severity in cotton. In conclusion, VdFTF1, which encodes a TF containing a Fungal_trans domain, regulates the gene expression of plant cell wall degradation enzymes in V. dahliae, which are required for full virulence on cotton.